Perancangan Antarmuka Aplikasi BCA Mobile Berbasis Heuristic Evaluation - Muhammad Rizqi Setyawan; Kurniawan D. Irianto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to evaluate the quality of the user interface (UI) and user experience (UX) of the BCA Mobile application using the Heuristic Evaluation method. The primary objective is to develop a design solution that is more effective, intuitive, and aligned with users’ needs in conducting digital banking activities. The evaluation focuses on key features such as fund transfers, balance information, transaction history, and transaction notifications. The results reveal several issues related to readability, navigation efficiency, and visual data security. By applying a heuristic-based approach, the study proposes improvements including the addition of Face ID for access code authentication, enhanced text contrast, and the replacement of the virtual account feature. The proposed UI/UX redesign aims to improve user comfort, efficiency, and security in accessing BCA Mobile's digital banking services.